Collaborative spaces for social transformation. A complex look at social configurations - Ávalos Rodríguez, Ileana (2017)
The collaborative spaces for social transformation are a proposal made by the authors with which they seek an approach and a different approach to the theories raised under the paradigm of modernity. Through an approach based on holism, complexity and systems theory, the bases for solidarity, respectful of otherness and inclusive spaces are given. The above implies ethical, aesthetic and political changes in the configurations in which they are developed. As this article seeks to present and offer a conceptual framework that facilitates a social transformation through collaborative spaces that are generated from different perspectives. With this proposal of collaborative spaces it is tried to approach the social configurations from a new perspective that includes the exercise of the human practices from the approach of the new paradigm. One of the main conclusions is that we recognize the importance of relationships that allow us to live in connection and recognition of otherness, from the complexity and also modifying the current social approach that is characterized by being individualistic and competitive.